The Profile of Students Reasoning in Junior High School with Extrovert Personality in Solving Mathematical Problems - Fury Styo Siskawati (Universitas Islam Jember, 2016)
The purpose of the research is to describe the reasoning of junior high school students with extroverted personality in solving math problems. The kind of this research is descriptive research with qualitative approach. The subjects of the research are three students of junior high school students in VII class with extrovert personality. The data collecting methods are documentation, interviews, observation, questionnaires, and test. The credibility of the data is test by using triangulation. Triangulation that used is time, subject and method. The results of the research are, the mathematics reasoning of extrovert subject include the collecting facts related to the problem but not writing all the facts that exist, only partially needed for the calculation process is written, then do the analysis but not detailed just what is needed for the next process is written, then make conjectures and propose arguments to strengthen the conjecture that has been proposed, however, the conjecture that is made is incomplete and detailed only partially, and for the last is to draw conclusions but not validate the conclusions that have been made. The whole process in the deployment is done by the subject but not maximally. The situation is supported by the basic nature of extrovert subject that easily bored, not an expert writing but more expert opinion verbally.Keywords: reasoning, problem solving, and extrovert personality